The Characterization of L-Asparaginase with Low L-Glutaminase Activity Produced by the Marine Pseudomonas sp. Strain GH-W2b - Woon-Jong Yu; Ha Young Lee; Yong Min Kwon; Seung Seob Bae; Grace Choi; Hyun-Ju Hwang; Dawoon Chung (Microbiology Research)
L-asparaginase (ASNase) hydrolyzes L-asparagine to L-aspartic acid and ammonia and has been used as an antitumor agent for the treatment of acute lymphoblastic leukemia. ASNase has also been used to mitigate the suspected carcinogenic effects of acrylamide in foods. Commercial ASNases currently used in the pharmaceutical and food industries are produced by microorganisms, such as bacteria and fungi. However, their toxicity and poor thermal stability limit their application. Therefore, identifying novel sources of ASNase is critical. In the present study, we identified an asparaginase-producing marine bacterial strain, GH-W2b, as a Pseudomonas species. Based on the plate assay results, GH-W2b produced ASNase with marginal L-glutaminase (GLNase) activity, which has been reported to cause adverse effects in clinical ASNases. The ASNase activity of GH-W2b was maximized at 50–65 °C and pH 7.0–8.5. Notably, the activities were consistent at a wide range of NaCl concentrations (0–15%) at 37 °C. In addition, compared to the control (no pre-incubation), ASNase activities were retained (>87%) by 2 h pre-incubation at 4–37 °C. Overall, our results suggest that GH-W2b ASNase has the potential to serve as a candidate for the development of salt-tolerant and/or alternative ASNases in pharmaceutical and food products.